Mingmu Xiaomeng Tablets Restore Autophagy and Alleviate Diabetic Retinopathy by Inhibiting PI3K/Akt/mTOR Signaling - Yuwei Fang; Kangpei Shi; Haining Lu; Lin Lu; Bo Qiu (Frontiers Media S.A., 2021)
Objective: To investigate the effect of Mingmu Xiaomeng tablets (MMXM) on the expression of phosphoinositide 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR)-related proteins in a diabetic rat model.Methods: Thirty-two male Sprague Dawley rats were randomly divided into four groups: normal control (NC), diabetic model (DM) control, MMXM, and calcium dobesilate (CD) Rats injected with streptozotocin (STZ) were used as an experimental diabetes model. After 14 weeks, autophagy and PI3K/Akt/mTOR signaling pathway proteins were detected by western blot. Glial fibrillary acidic protein (GFAP) expression in Müller cells was examined by immunohistochemistry. Retinal function was evaluated with electroretinography, and retinal ultrastructure was observed by transmission electron microscopy. Serum cytokine levels were detected with protein chip technology.Results: MMXM restored autophagy by decreasing the protein expression of LC3-II and p62 and reducing the phosphorylation of PI3K, Akt, and mTOR, thus promoting autophagy. MMXM decreased GFAP expression in retinal Müller cells; restored electrophysiology indexes and retinal ultrastructures; and reduced serum levels of interleukin (IL)-1β, IL-4, IL-6, tumor necrosis factor-α, and vascular endothelial growth factor.Conclusion: MMXM may protect the diabetic retina by inhibiting PI3K/Akt/mTOR signaling and enhancing autophagy.